The Legal Regulation of Voluntary Team in Iraq (Journal of the College of Basic Education, 2022)
The reason for choosing this topic is that the voluntary team has become a real social phenomenon in Iraq, with no legislation regulating its provisions and this research derives its importance from its association with addressing this active phenomenon, which has been shaped by the urgent need to play roles in various community fields by civilian activists. This research sought to highlight the legal adaptation of the nature of the voluntary team's work and to determine the position of Iraqi legislation on it, as well as to indicate theoretical and practical solutions and perceptions of legal treatment to protect the voluntary team in Iraq. The main problem of the research lies in the extent to which the Iraqi NGO law in force understands the rules and provisions of the voluntary team as a form of mass non-governmental organization. One of the most important results is that the voluntary team and the NGO are similar in volunteering, bringing together a group of people and some objectives such as service delivery, while there is a clear difference in structure, administrative and institutional organization, conditions for formal registration and the objectives of their work. The Voluntary team enjoys civil protection in addition to criminal protection. One of the most important recommendations is the enactment of a law regulating the provisions of voluntary teams in Iraq. However, the Non-Governmental Organizations Act No. 12 of 2010, which is in force, can be amended to regulate the actions of voluntary teams and the rights and obligations of volunteers and to adapt the reality of their work in that light. and to promote a culture of volunteering among young people and to instill in them the spirit of collective action through various means.